Hubungan antara Asupan Gizi dengan Status Gizi Remaja Putri - Hartaningrum, Putu Intan; Sutiari, Ni Ketut; Dwijayanti, Lina Anggaraeni (Jurnal Kesehatan, 2021)
Three burdens of malnutrition, namely undernutrition, overnutrition, and lack of macronutrients are problems faced by adolescents in Indonesia. Nutritional problems related to development and growth are often experienced by adolescents because the adolescent's body requires more energy and nutrients than children. Previous studies on nutritional intake and nutritional status in adolescents reported inconsistent results. This study aims to determine the relationship between nutritional intake and nutritional status in adolescent girls in Buleleng Bali. This study uses a cross-sectional analytic observational design conducted in two high schools in Buleleng Regency with 163 respondents. The instruments used in this study were a questionnaire, 2x24 hour food recall, weight measurement with a weight scale, height measurement with a mechanical meter, and the World Health Organization (WHO) AnthroPlus software to calculate the body mass index by age (z-score). Spearman correlation test was performed for bivariate analysis and multiple linear regression for multivariate analysis. Bivariate analysis showed that the variables of fat intake (p-value=<0,001) and total energy intake (p-value=0,008) showed a significant correlation with the z-score. In multivariate analysis, the variable that showed a significant relationship with the z-score was fat intake (Î²=0,023, 95%CI=0,013-0,033, p-value=<0,001). Nutritional intake that has a significant relationship with nutritional status in adolescent girls in Buleleng Regency is fat intake. Limitation of fat consumption needs to be done.